Pan-cancer clinical impact of latent drivers from double mutations - Bengi Ruken Yavuz; Chung-Jung Tsai; Ruth Nussinov; Nurcan Tuncbag (Communications Biology, 2023)
A statistical methodology is used to identify potential ‘latent driver’ mutations from public cancer bulk sequencing data.